(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. The development of mechanisms for public investment in regional development projects is an important task of modern economic policy in the context of globalization, decentralization, and the growing role of regions as centers of economic growth. The effectiveness of these mechanisms affects not only the progress of individual territories but also the sustainable development of the national economy as a whole. The necessary to study this topic is due, first, to the complexity of the process of forming public investment mechanisms: modern economic theory offers a wide range of approaches to solving this problem, but their adaptation to the realities of Ukraine requires additional research. Secondly, the insufficient use of the conceptual framework: the formation of new investment mechanisms should be based on scientifically sound concepts and take into account the best international practices. Third, the lack of an integrated approach: existing mechanisms are fragmented and do not always take into account the specifics of the regions, which reduces their effectiveness. Fourth, the low level of involvement of innovative financial instruments, such as public-private partnerships, development bonds, or grant funding. Fifth, the need to prepare policy recommendations: the results of the study will contribute to the development of effective tools to support regional development based on scientific analysis. Objective. The purpose of the article is to comprehensively study and build mechanisms for public investment in regional development projects. Methods. The methodological basis of the study is the theoretical provisions of economic and financial sciences, works of famous scientists. To solve the research tasks, the paper uses the dialectical method of scientific knowledge, methods of empirical and theoretical research, in particular, conceptual and logical analysis and a systematic approach. Results. Practical testing of the state policy, including at the regional and local levels, involves the use of both complex and purely functional mechanisms, tools, and means. The mechanism as the most systematic means of regulation is considered as a controlled set of elements (subjects, objects, purpose, goals, objectives, functions, principles, means, measures, tools for monitoring, control and adjustment, etc.) used to implement and solve public administration tasks in the relevant functional or other sphere of development of the state, its regions, territories. At the same time, the achievement of the general goal and policy objectives in such a complex area as public investment in regional development projects requires the use of a certain holistic system of mechanisms for such purposes, the basic of which are: institutional and legal, institutional and organizational, infrastructure, economic, social and psychological, monitoring and control. Conclusions. The formation and implementation of each of these mechanisms have their own clearly defined goals and objectives, which are generally subordinated to the general goal of the State policy in the analyzed area - the public investment institution’s acting as a powerful factor in the development of communities, territories, and regions of the country.